AS POLÍTICAS PÚBLICAS E O EXPERIMENTALISMO INSTITUCIONAL: O Programa Bolsa-Família reformado - Biasoli, Felipe Iraldo de Oliveira (2014)
This thesis unfolds in two frameworks. The first of them is related with criticism to the main theoretical models of analysis in Public Policy currently professed, based in principles arising from changes in the Human Sciences during the last century: devotion to the model of the hard sciences; commitment to objectivity; trust in the power of formal analysis; aversion to transformative ideas (Chapter 1). The second framework analyses the thesis of the transformative politics presented by institutional experimentalism, which exposes the playing field of high-energy politics. Based on the social theory of Roberto Mangabeira Unger, this kind of politics is distinct both from the Marxism revolutionary politics and from the routine politics of marginal redistributive adjustments (Chapter 2). Finally, this thesis argues that public policies can be based in a transformative theoretical model in order to be able to rethink innovative ways for Brazilian social policies such as Programa Bolsa Família (Chapter 3)